2022
DOI: 10.3390/ijerph19158943
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Mortality among Community-Dwelling Older Adults in Malaysia: A 5 Years Longitudinal Study

Abstract: With older adults accounting for 10.7% of the Malaysian population, determining the predictors of mortality has now become crucial. Thus, this community-based longitudinal study aimed to investigate the predictors for mortality among community-dwelling older adults using a wide range of factors, including clinical or subclinical. A total of 2322 older adults were interviewed and assessed by trained fieldworkers using validated structured questionnaires. The questionnaire consisted of information on socio-demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The followup duration of cohorts ranged from 5 to 40 years. Twenty-five studies reported the results for total fiber, [28][29][30][31][32][33][49][50][51][52][53][54][55][56][57][60][61][62][63][64][66][67][68][69][70] 10 studies reported the results for fruit and vegetable fiber, 30,31,33,50,54,56,57,[63][64][65] 10 for cereal fiber, 30,31,33,50,51,[56][57][58]64,65 eight for soluble fiber, 30,31,33,50,52,55,…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The followup duration of cohorts ranged from 5 to 40 years. Twenty-five studies reported the results for total fiber, [28][29][30][31][32][33][49][50][51][52][53][54][55][56][57][60][61][62][63][64][66][67][68][69][70] 10 studies reported the results for fruit and vegetable fiber, 30,31,33,50,54,56,57,[63][64][65] 10 for cereal fiber, 30,31,33,50,51,[56][57][58]64,65 eight for soluble fiber, 30,31,33,50,52,55,…”
Section: Resultsmentioning
confidence: 99%
“…30,31,33,[63][64][65] Fourteen studies were conducted in European countries, [28][29][30]33,49,53,56,[60][61][62][64][65][66][67] seven in the US, 51,52,55,58,59,63,69 and seven in Asia. 31,32,50,54,57,68,70 Three studies were conducted exclusively on women, 51,59,65 three on men, 28,64,67 and the others on both sexes. Nineteen studies used a food frequency questionnaire (FFQ) for dietary assessment, 28,30,31,[49][50][51]53,54,[56][57]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations